The ancient cliff dwellers of Mesa Verde - Arnold, Caroline; Hewett, Richard (New York : Clarion Books, 1992)
Discusses the native Americans known as the Anasazi, who migrated to southwestern Colorado in the first century A.D. and mysteriously disappeared in 1300 A.D. after constructing extensive dwellings in the cliffs of the steep canyon walls.
Includes index.
Wilson's Children
Elem. School Library Collection
School Library Journal
6.3
5-8
Keywords: Pueblo Indians -- History -- Juvenile literature; Pueblo Indians -- Social life and customs -- Juvenile literature; Mesa Verde National Park (Colo.) -- Juvenile literature; Pueblo Indians; Indians of North America -- Southwest, New; Cliff dwellings -- Southwest, New; Mesa Verde National Park (Colo.); Pueblo Indians; Mesa Verde National Park (Colo.); Indians of North America; Cliff dwellers and cliff dwellings